Effect of polystyrene on poly(ethylene terephthalate) crystallization - Wellen,Renate Maria Ramos (2014)
Blends of poly(ethylene terephthalate) (PET) and polystyrene (PS) with PS content ranging from 0% to 60% by weight, were compounded in a laboratory internal mixer, followed by quenching into iced water, resulting in substantially amorphous compounds. Blend morphology was analyzed by scanning electron microscopy (SEM). Standard differential scanning calorimetry (DSC) was used to study the cold crystallization and melting behavior of PET and PET/PS blends. SEM micrographs show a two-phase structure made up with spherical PS particles dispersed in a PET matrix. DSC scans showed that crystallization of PET is affected by the heating rate and by the addition of even small amounts of PS. In particular, the rate of cold crystallization of PET is significantly reduced by the incorporation of 1% of PS, attributed to the anti-nucleating effect of PS on PET. The amount of PET crystallized and the melting characteristics (temperature, rate) are not significantly affected by either PS content or heating rate.